Sistem Penunjang Keputusan Untuk Penentuan Ketua Ekstrakurikuler Menggunakan Metode Profile Matching - Nazmi Uliah; Bakhtiar Rifai; Sopiyan Dalis (JURNAL TEKNIK KOMPUTER AMIK BSI, 2021)
The role of the School Extracurricular (EKSKUL) in a junior high school, high school, vocational high school/equivalent has an important function in improving the quality of school environment, proper selection in determining the Chair of the EKSKUL is very necessary in order to be able to protect and become role models for students in the environment. school. The absence of a fixed application of specific criteria, and the absence of voter understanding in choosing the extracurricular chair according to the criteria, make this study more helpful in applying the criteria using the profile matching method. It is hoped that it can help the existing schools at MA Tarbiyah Islamiyah in facilitating the selection of the chairman of EKSKUL. The criteria that have been determined are Behavioral Aspects, Responsibility Aspects, Communication Aspects. The assessment was carried out by filling out a Likert scale questionnaire by the respondents, where Scale 5 = Very Good, Scale 4 = Good, Scale 3 = Doubtful, Scale 2 = Disagree, Scale 1 = Strongly Disagree. The results were processed using the profile matching method, and based on the results obtained, the top-ranking was Dhiyah Fathiyyah with a final score of 4.86. So it can be concluded that there is an influence in determining the selection of extracurricular chairman using the profile matching method according to the existing criteria.